A Curriculum for Perioperative Nurse Deployment During a Pandemic. (3rd February 2021) - Hemingway, Maureen W.; Silvestri, Sandra
ABSTRACT: As the coronavirus disease 2019 (COVID‐19) pandemic spread around the world, the US Surgeon General called for the cancellation of elective surgeries. At a large academic medical center in the Northeast, there was a resulting surplus of perioperative nurses who were deployed to inpatient units in need of skilled nursing care for a surge of COVID‐19 patients. To prepare them for deployment to inpatient units, perioperative leaders developed a core curriculum to ensure that the OR nurses possessed the skills and knowledge required to successfully care for patients outside the OR with the same level of care and compassion that they provided to perioperative patients. The leaders employed available resources at the hospital to design and implement the course in a short amount of time. This article describes the development of a curriculum for OR nurses to manage a surging patient volume on inpatient units because of the COVID‐19 pandemic.